Virtual screening of compounds derived from Garcinia pedunculata as an inhibitor of gamma hemolysin component A of Staphylococcus aureus - Chowdhury, Tarali (Bangladesh Journal of Pharmacology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> With the emergence of multi-drug resistant pathogens at alarming frequency, there has been an increase interest in the development of novel drugs from natural resources. The use of higher plants and preparations made from them to treat infections is a longstanding practice in a large part of the population, especially in the developing countries, where there is dependence on traditional medicine for a variety of ailments. The virtual screening method was used in this study to analyze the docking and inhibitory activities of some natural bioactive compounds present within Garcinia pedunculata against hemolysin toxin of Staphylococcus aureus, gamma-hemolysin component A hlgA. The study resulted in identifying compounds 1,3,6,7-tetrahydroxyxanthone and garcinone D with high binding affinity towards the target protein revealing them as potent inhibitors that could be further used to create new drug source in the treatment of staphyloccocal infections. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";} --> <!--[endif] -->